Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan pada Divisi Produksi di PT Multi Teknik Telaga Indonesia - Hanna Putri Yulia; Ani Rakhmanita (Journal of Management and Social Sciences, 2023)
Human resources (HR) play an important role in a company because they can influence the company's efficiency and effectiveness. This research was conducted by exploring the perceptions of PT employees. Multi Teknik Telaga Indonesia to determine employee performance and the factors that influence it, namely leadership style and organizational culture. This research is located on Jl. Daan Mogot 119 Block C12 Jakarta. The research method used is a quantitative method. The type of research approach is using field research, by carrying out activities such as distributing questionnaires to respondents, processing data and analyzing data obtained from respondents. The number of samples taken from PT. Multi Teknik Telaga Indonesia as many as 30 respondents. The data analysis technique used is multiple linear regression analysis and the hypothesis in this study was tested using the Partial Test (T) and Simultaneous Test (F). The results of the analysis show that Leadership Style and Organizational Culture have a positive and significant effect simultaneously on Employee Performance in the Production Division at PT. Multi Teknik Telaga Indonesia. Partially Leadership Style (X1) has a positive but not significant effect on Employee Performance (Y). Furthermore, Organizational Culture (X2) has a positive and significant effect on Employee Performance (Y).